JOURNALIST QUESTIONS TECHNIQUE IN WIRITING ABILITY WITH NARRATIVE TEXT - Disky Prayoga; Herlina Herlina; Evi Rosmiyati (Esteem Journal of English Education Study Programme, 2023)
The purpose of the study was to describe how the students use the journalist questions technique in writing ability in narrative text and to describe the students’ responses produced in the class, the researcher would use written responses. This study used qualitative research, related to collect and analyse the data in the various forms, especially non-numeric forms. The researcher chosed this approach because the study's objectives include demonstrating knowledge of detailed and in-depth sample evaluation as well as class XI students at Senior High School PGRI 2 Palembang. The result showed that the narrative text was an idea from the students to understand and how to use journalist questions in writing with narrative text. The result showed that the 11th graders have a positive response towards the use of journalist questions in writing ability with narrative text. As a results of the students’ responses produced in the class, the researcher found that students showed a range of behaviors that demonstrated their writing ability in narrative text and evaluation of the texts as well as of their responses. The class had a relatively sufficient feedback which provided. Students demonstrated a high comprehension from the text. The amounts of tasks in the text clearly aimed to reach the goal. Students’ responses in written form also showed that they were trained to be more capable in writing.